Editorial Pointers. - Crawford, Dione (Communications of the ACM, 2004)
It is informed that there is a growing faction of software developers dedicated to empowering end users with the tools to become, in fact, software developers. The goal of end-user development is to provide users the freedom and ability to create their own software solutions. It is a movement propelled by changes in business, software evolution, and the increasing need to tailor complex programs to personal requirements and expectations. In the current issue of the journal "Communications of the ACM," a hard look is also taken into the filtering software and the methods for evaluating its effectiveness. The articles published in the current issue also inspect the strengths and weaknesses of wireless technologies. In her article, Meg McGinity chronicles the weaknesses in telecommunications technologies revisited by the 9/11 commission and some of the wireless networking issues that have emerged. In the article "Digital Village," Hal Berghel examines the use of war driving, or as he describes it, the "art of monitoring wireless traffic."